Edukasi Dampak Pernikahan Dini Dan KDRT Bagi Anak - Nur Farida Kusumawati; Mohamad Fahris Hidayat; Mohammad Ifan Afiffudin; Puspita Nuur Sanubari; Rahmat Dwi Febriansyah; Sebastianus Prihanggara; Siti Sri Islamiati; Dwi Putri Maulidah; Ekowati Ekowati; Eric Syahadad Fladimir; Fajarwati Dian Wahyuni; Mochamad Amirulloh Sayfudin; Pupung Ferdi Firmansyah; Ayu Triswana; Sriyatun Sriyatun; Muji Sulistianingsih; Sigittrio Nugroho; Wahyu Purna Wigati; Johan Adi Firman Kuncoro; Moch. Dicky Oktafian; Feryk Bagoes Wardana; Novalda Ega Mahesta; Ersita Septiana; Eirene Stefani Athalia Sabrina (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Violence against children is an arbitrary act that can harm children both physically and psychologically. One of the causes of domestic violence against children is early marriage. Children who witness domestic violence or are victims of violence themselves have long-term physical and mental health risks. Children who witness domestic violence between their parents are also at higher risk of committing domestic violence in the future. The solution to preventing early marriage and child domestic violence can be to collaborate with relevant agencies and institutions in the field to hold youth training regarding the impact of early marriage and parenting training for parents regarding how to raise their children well.